Answer:
5/9
Step-by-step explanation:
Let the denominator be x and numerator be y.
Given, numerator is 4 less than denominator
=> y = x - 4 ...(1)
When 5 is added to both:
Numerator = y + 5 , and, denominator = x + 5
Now their ratio is 5/7.
=> (y + 5)/(x + 5) = 5/7
=> 7(y + 5) = 5(x + 5)
=> 7y + 35 = 5x + 25
=> 7y - 5x = 25 - 35
=> 7(x - 4) - 5x = -10 {y=x-4}
=> 7x - 28 - 5x = -10
=> 2x = 18
=> x = 9
Thus,
Fraction is y/x = (x-4)/x = (9-4)/9 = 5/9
Answer: x > 6
Step-by-step explanation: -4(2x+2) < -40
-8x - 8 < -40
+8 +8
-8x < 48
/-8x /-8x
x > 6 *The less than sign got flipped to a greater than sign because we divided by a negative.
0.5 of a mile - since 5,280ft = 1 mile and half of 5,280 is 2,640
Answer:
Once the equation is in standard form, factor the quadratic expression. 2x2 + 7x + 3 = 0 (2x + 1)(x + 3) = 0. Using the Zero Product Property set ...
2x2 + 7x = -3
2x2 + 7x + 3 = 0
Once the equation is in standard form, factor the quadratic expression.
2x2 + 7x + 3 = 0
(2x + 1)(x + 3) = 0
Using the Zero Product Property set each factor equal to 0 and solve for x.
2x + 1 = 0
2x + 1 - 1 = 0 - 1 x + 3 = 0
2x = -1 x + 3 - 3 = 0 - 3
2x 2 = -1 2 x = -3
x = -1 2
The solutions to the equation are -1 2 and -3.